2021
DOI: 10.1002/srin.202100413
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Spatial Distribution of Argon Bubbles in a Steel Slab Continuous Casting Strand

Abstract: Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…Figure 3 shows the bubble distribution within the mold at the casting speed of 0.63 m/min and argon flow rate of 0.638 L/min at the SEN. It can be seen that most of the bubbles floated near the SEN, especially the large bubbles, while the small bubbles moved along with the jet flow to the narrow face because of the effect of buoyancy, which is consistent with the flow characteristics calculated by Zhang [21] and Yang [28]. The bubble diameters within the mold obtained by the current model are shown in Figure 3b, which indicates that both the distribution and penetrating depth of argon bubbles agree well with the experiment.…”
Section: Modeling Validationsupporting
confidence: 88%
See 2 more Smart Citations
“…Figure 3 shows the bubble distribution within the mold at the casting speed of 0.63 m/min and argon flow rate of 0.638 L/min at the SEN. It can be seen that most of the bubbles floated near the SEN, especially the large bubbles, while the small bubbles moved along with the jet flow to the narrow face because of the effect of buoyancy, which is consistent with the flow characteristics calculated by Zhang [21] and Yang [28]. The bubble diameters within the mold obtained by the current model are shown in Figure 3b, which indicates that both the distribution and penetrating depth of argon bubbles agree well with the experiment.…”
Section: Modeling Validationsupporting
confidence: 88%
“…The results indicated that the proportion of large bubbles and average bubble diameter in the upper recirculation zone decreased with the increment of water flow rate and increased with the increment of gas flow rate. Meanwhile, similar conclusions were also reached by Zhang [21]: it was confirmed that increasing argon gas flow rate promotes bubble breakage, and increasing casting speed promotes bubble coalescence. The aforementioned study has great significance in understanding the flow pattern and bubble distribution within a mold under argon injection; however, most of these works injected the argon through the top of the SEN inlet.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…[33,34] For the gas injection method, it can also offset the pressure drop in the SEN and reduce the reoxidation of the molten steel caused by the nozzle suction. The behavior of argon bubbles has been widely studied inside the CC mold at different casting parameters, including the casting speed, [35,36] argon flow rate, [37][38][39] and submergence depth of the SEN. [40] Recent studies on the bubbly flow inside the SEN are summarized in Table 1, including investigations performed by the physical modeling, mathematical modeling, and industrial trials. However, the effect of the SEN bottom shape on the size distribution of argon bubbles was rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers (Li et al , 2020; Liu and Li, 2018; Zhang et al , 2006) have recognized that metal flow in the mold is a major aspect influencing the quality of continuously cast products. The flow pattern of the mold is influenced by various process parameters such as nozzle shape, nozzle submergence depth (Ma et al , 2021), argon gas injection rate (Liu et al , 2022; Yin and Zhang, 2022) and casting speed. Additionally, it has been found that electromagnetic (EM) forces can instant alter the flow pattern, enhancing the microstructure of material and assisting in removing impurities from molten steel.…”
Section: Introductionmentioning
confidence: 99%